European integration and the prospects for the Baltic states - Egidijus Vareikis (Politologija)
This article debates a large number of problems. One of the essential problems is the chances of the Baltic States in the process of the European Integration. Viewing purposes of entering EU and NATO as the main destinations of the Baltic States' foreign policy, the author propounds a conceptual review on this problem (so far as it does not restrict itself within the wish and the attitude of the three Baltic States, but reaches far beyond it and inevitably postulates universal complexity of this problem). Consequently, the author proceeds to the elucidation of the issues due to which the identification of the geopolitical status of the Baltic States becomes problematic.